Bibliometric Analysis: Performance Measurement From 2003-2023 Using Vosviewer - Ummah, Feby Farichatul; Kurniawan, Asep; Othman, Nur’Ayyshah Hui; Mulyati, Sri (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2024)
Performance measurement has become a very important topic in modern business management. This study aims to determine the research trends around performance measurement in general and specifically in Indonesia and Malaysia from 2003-2023. As well as to determine opportunities or potential for future research. The method used is bibliometric analysis in the form of literature review related to performance measurement. Data was collected from the Scopus database using the keywords “performance AND measurement AND (Indonesia OR Malaysia)” and obtained 2,358 publications from 2003-2023. However, researchers took 205 documents that were appropriate and relevant to the criteria of this study. Then the researcher used VOSviewer software and Microsoft Excel assistance to analyze and visualize the database obtained. The results showed that the trend of research on performance measurement from 2003-2023 showed significant dynamics. The keyword “performance measurement” is divided into 7 clusters. The publisher that publishes the most publications is Inderscience Publishers, while the most productive author is Kusrini, E. The most common type of publication in scientific publications on “performance measurement” is journal articles. The most productive country/region conducting research is Malaysia with a total of 101 documents published. This research also identified the top ten articles with the most citations, with Agus, A., Hajinoor, M.S. being the most cited article. Potential or future research opportunities could focus on new topics that are beginning to emerge in the literature, such as “Supply chain performance”, “Competitive advantage”, and “Financial performance”. As well as the analysis of the literature that discusses performance measurement in Indonesia and Malaysia shows that there are differences in trends and research focus in the two countries.